If a + b + c = 1 and a 1 + b 1 + c 1 = 3 , where a , b and c are non-zero reals , then find ( a + b ) a b + ( b + c ) b c + ( c + a ) c a .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Instead of adding a term to each pf the brackets, we could alternatively substitute ( b + c ) with ( 1 − a ) , etc. Great solution. +1
good approach to the problem..+1
Just one thing.... Your solutions are not scrollable at all on mobile.and that's why many people (including me) are not able to see the full line at once on mobile... So I request you to either use \[ \) or give line breaks at small intervals..... Thanks.
Log in to reply
Thanks for the feedback. I have redone the solution. The problem came from {align}. \ [ \ ] will make the solution very long.
(1/a)+(1/b)+(1/c)=3
(ab+bc+ca)/abc=3
ab+bc+ca=3abc ---------Eq. 1
We have to find (a+b)(ab)+(b+c)(bc)+(c+a)(ac)
Multiplying and dividing by abc, we get
abc((a+b)/c) + (b+c)/a + (c+a)/b)
From a+b+c=1...
a+b=1-c
b+c=1-a
c+a=1-b
So abc((a+b)/c) + (b+c)/a + (c+a)/b)=
abc((1-c)/c) + (1-a)/a + (1-b)/b)=
abc( 1/a) + (1/b) + (1/c) - 3) =
((abc(ab+bc+ca))/abc) -3abc=
ab+bc+ca-3abc
From Eq. 1 ,3abc = ab+bc+ca
So our answer is (ab+bc+ca) - (ab+bc+ca) = 0
(Sorry for not using latex, I'm still learning latex, plus I'm posting this using my phone).
your solution is perfect..+1 try learning latex
Nice same solution +1 :)
Yey, new solution
a + b + c = 1 ⟹ a + b = 1 − c , b + c = 1 − a , a + c = 1 − b
( a + b ) ( a b ) + ( b + c ) b c + ( a + c ) a c = ( 1 − c ) a b + ( 1 − a ) b c + ( 1 − b ) a c = a b − a b c + b c − a b c + c a − a b c = a b + b c + c a − 3 a b c
Now, since a 1 + b 1 + c 1 = 3 , multiplying both sides by a b c gives us
a b c ( a 1 + b 1 + c 1 ) = 3 a b c
a a b c + b a b c + c a b c = 3 a b c
a b + b c + c a = 3 a b c ⟹ a b + b c + a c − 3 a b c = 0
Therefore, our answer is 0 .
I f y o u r e a d t h i s , c o n g r a t u l a t i o n s ! E i t h e r y o u t u r n e d o f f L a T e X o r h a p p e n e d t o p u t y o u r c u r s o r o v e r i t .
good one..+1
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Algebraic Identities
It is given that:
a 1 + b 1 + c 1 = 3 ⟹ a b c a b + b c + c a = 3 ⟹ a b + b c + c a = 3 a b c
Now, we have:
( a + b ) a b + ( b + c ) b c + ( c + a ) c a = ( a + b + c ) a b + ( a + b + c ) b c + ( c + b + a ) c a − 3 a b c = ( a + b + c ) ( a b + b c + c a ) − 3 a b c Note that a + b + c = 1 = a b + b c + c a − 3 a b c Note that a b + b c + c a = 3 a b c = 0